Analysis of the Achievement of Fourth Grade Students at SDN 029 Cilengkrang in Solving Multiplication Problems (Current Research in Education: Conference Series Journal, 2024)
This study aims to analyze elementary school students' ability to solve multiplication problems and identify the types of errors they make. The research subjects consisted of 25 fourth-grade students from SDN 029 Cilengkrang. The research method used is a case study with the instrument being a written test containing five contextual questions, but the detailed analysis is focused on question number 3. The research results show that 28% of students are in the high ability category, 48% are in the medium category, and 24% are in the low category. The most common errors made by students with moderate and low abilities include errors in modeling word problems, calculation procedure errors, and errors in transforming verbal sentences into mathematical model form. These findings indicate that high-ability students are capable of understanding multiplication concepts and procedures, while some students are still focused on memorizing multiplication results and have not fully grasped their conceptual meaning. Therefore, learning should focus on strengthening the understanding of multiplication concepts thru contextual activities and visual representations to improve students' overall conceptual and procedural abilities.